2004
DOI: 10.1113/jphysiol.2004.060715
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic relationship between starburst amacrine cells and direction‐selective ganglion cells in the rabbit retina

Abstract: We investigated the dendritic relationship between starburst amacrine cells (SAs) and morphologically and physiologically characterized ON and ON-OFF direction-selective ganglion cells (DSGCs) in the rabbit retina. ON and ON-OFF DSGCs were found to exhibit tight dendritic cofasciculation with the SA plexus, visualized by immunolabelling of the vesicular acetylcholine transporter (VAChT). The degree of cofasciculation of both types of DSGC dendrites and SA plexus was found to be significant, unlike the relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
47
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 24 publications
8
47
1
Order By: Relevance
“…While it is true that the dendrites of α ganglion cells often appear, especially at low power, to run with the cholinergic processes, our analysis showed that this did not occur more than for a randomly oriented cell (see also Dong et al, 2004). In other words, the association of α ganglion cell dendrites with the cholinergic matrix does not exceed that of a random line drawn across the field.…”
Section: Co-fasciculation With the Cholinergic Matrixmentioning
confidence: 51%
See 4 more Smart Citations
“…While it is true that the dendrites of α ganglion cells often appear, especially at low power, to run with the cholinergic processes, our analysis showed that this did not occur more than for a randomly oriented cell (see also Dong et al, 2004). In other words, the association of α ganglion cell dendrites with the cholinergic matrix does not exceed that of a random line drawn across the field.…”
Section: Co-fasciculation With the Cholinergic Matrixmentioning
confidence: 51%
“…Starburst amacrine cells are relatively numerous wide-field cells with a large overlap producing a dense cholinergic matrix, and it has previously been shown that DS ganglion cells co-fasciculate with the dendrites of starburst amacrine cells. In one model of directional selectivity, it was reported that the null side of DS ganglion cells preferentially associated with starburst amacrine cells (Fried et al, 2002), but in a more recent study, the specificity of these connections could not be confirmed (Dong et al, 2004). Both dendritic trees of ON/OFF DS ganglion cells ran within the cholinergic matrix with no apparent preference for the preferred or null directions.…”
Section: Co-fasciculation With the Cholinergic Matrixmentioning
confidence: 88%
See 3 more Smart Citations